2022
DOI: 10.1111/aor.14341
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of spatial patterns using electrotactile stimulation via a multi‐pad electrode placed on the torso

Abstract: Background Tactile stimulation can be used to convey information to a user in different scenarios while avoiding overloading other senses. Tactile messages can be transmitted as spatial patterns, potentially allowing for a high information throughput. The aim of the present study was to design and test different encoding schemes to determine the best approach for conveying spatial patterns. Methods Encoding schemes with simultaneous (SIM) and sequential pad activation (SEQ) were evaluated, including four SEQ v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…During the spatial recognition test ( Figure 5 a), the pads facing the ventral side of the torso were on average better recognized compared to the pads facing the dorsal side (SR: 83.3% vs. 79.3%), which agrees with the findings in the literature that the ventral side of the torso is more sensitive and accurate [ 39 , 54 ]. The side of the body (i.e., front or back) was rarely misinterpreted, and most errors were made along the vertical axis of the electrode.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…During the spatial recognition test ( Figure 5 a), the pads facing the ventral side of the torso were on average better recognized compared to the pads facing the dorsal side (SR: 83.3% vs. 79.3%), which agrees with the findings in the literature that the ventral side of the torso is more sensitive and accurate [ 39 , 54 ]. The side of the body (i.e., front or back) was rarely misinterpreted, and most errors were made along the vertical axis of the electrode.…”
Section: Discussionsupporting
confidence: 87%
“…The electrode was designed based on the project requirements. The preliminary psychometric evaluation of this system confirmed that this design choice was suitable for the application of interest [ 54 , 55 , 56 ]. The electrode design considered six smaller circle-shaped pads and two larger pads with rounded rectangle shape ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…17 This placement was a specific requirement of first responders to minimize potential interference with gear (e.g., backpacks, face masks, and armbands) and movement. 17,22 The electrode comprised six circle-shaped active pads arranged in a 3 × 2 pad matrix and two rectangular active pads with rounded corners, each of them surrounded by a reference pad forming eight concentric pad pairs (Figure 1A).…”
Section: Methodsmentioning
confidence: 99%
“…10,17 In addition, the system could convey many messages with high reliability by encoding the information using a spatiotemporal approach with sequential activation of pads. 22 However, the proposed method was tested while subjects were fully focused on interpreting electrotactile stimulation, whereas the envisioned application of the system (i.e., first responders) implies that information is delivered in situations where the user divides his/her attention across several tasks. 10 Although studies have shown that haptic communication suffers from lower performance when performing concomitant tasks, there is not much literature on how to optimize haptic communication during multitasking.…”
Section: Introductionmentioning
confidence: 99%